(untitled) (Comparatismi, 2025)
Woke ideology, an extreme version of political correctness, is characterized by some distinctive features: the identity paradigm, victim ideology, puritanism. Three elements that are found in the movement #metoo and in its French variant #balancetonporc, whose birth coincides precisely with the consolidation of the very definition of the term woke. Three stories linked to the world of cinema, and particularly to France, tell us the radicalization of a clash and the risk of a new totalitarianism.